2020
DOI: 10.3390/jcm9103320
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effect of Adapting the Vertical Position of Implants on Peri-Implant Health: A 5-Year Intra-Subject Comparison in the Edentulous Mandible Including Oral Health-Related Quality of Life

Abstract: Despite high success rates of dental implants, surface exposure may occur as a consequence of biologic width establishment associated with surgery. This prospective split-mouth study evaluated the effect of early implant surface exposure caused by initial bone remodeling on long-term peri-implant bone stability and peri-implant health. Additionally, Oral Health-Related Quality of Life (OHRQoL) was assessed by means of the Oral Health Impact Profile-14 (OHIP-14). Twenty-six patients received two non-splinted im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The effect of adapting the vertical position of the implant in relation to the soft tissue thickness is published in several studies. [17][18][19][20][21][22] It could prevent early implant surface exposure by initial bone remodeling. The results of this study are in according to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of adapting the vertical position of the implant in relation to the soft tissue thickness is published in several studies. [17][18][19][20][21][22] It could prevent early implant surface exposure by initial bone remodeling. The results of this study are in according to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…The biologic width is an essential space that must be maintained to ensure periodontal health in any dental prosthetic restorations [ 47 ]. Hence, it is important to preserve the periodontal health and remove any irritation that might damage the periodontium such as may occur during prosthetic restorations [ 45 , 48 ]. Considering this, an iatrogenic fixed dental prosthesis that is constructed in violation of the biologic width predisposes the development of subgingival caries in the involved teeth and results in an uncontrolled inflammatory process and periodontal tissue destruction [ 47 ].…”
Section: Biologic Width and Gingival Biotype Considerations In Fixed ...mentioning
confidence: 99%
“…30 Counteracting marginal bone modification by adapting the vertical position of the implant may limit EMBL to bone remodeling, avoiding treated implant surface exposure. 31,32 However, controversial information is present in literature regarding the relationship between marginal bone stability and subcrestal implant placement. Some authors observed that implant placement 1 or 2 mm subcrestally is associated with minimal marginal bone modification, 33,34 whereas other investigators demonstrated that EMBL is directly associated with implant insertion depth.…”
Section: Introductionmentioning
confidence: 99%
“…According to Linkevicius and coworkers, when the implant platform is positioned subcrestally, EMBL may occur either only above the implant neck (bone remodeling) or may also involve bone surrounding the implant neck and underlying implant surface (bone loss) 30 . Counteracting marginal bone modification by adapting the vertical position of the implant may limit EMBL to bone remodeling, avoiding treated implant surface exposure 31,32 …”
Section: Introductionmentioning
confidence: 99%